Modifikasi Algoritma Sattolo Shuffle Untuk Mengacak Soal Pada Aplikasi Ujian Online - Nasution, Surya Darma; Mesran, Mesran (Forum Kerjasama Pendidikan Tinggi, 2025)
The use of Computer-Based Testing (CBT) systems has become a popular evaluation method due to its efficiency and ability to accelerate the assessment process. However, challenges such as cheating and the similarity of question sequences among participants still frequently occur. This study aims to design and implement a modified Sattolo Shuffle algorithm with the addition of a Linear Congruential Generator (LCG) as a source of random numbers in the exam question randomization process. The Sattolo Shuffle algorithm was chosen because it produces a single cyclic permutation that ensures each question element is repositioned, reducing the potential for recurring patterns. The LCG is used to generate random indices deterministically but variably, based on specific parameters and an initial value (seed) derived from the participant’s serial number. The implementation was carried out in a web-based CBT system consisting of 50 questions in each exam session. Testing on three participants showed that the generated question sequences were completely different, with no identical orders found. Each participant received a unique combination of questions with an even distribution of question positions. Initial results demonstrate the algorithm's effectiveness in increasing question variation and preventing duplication, making it a potential solution to enhance security and fairness in CBT administration. This research is expected to contribute significantly to the development of more randomized, fair, and cheat-resistant online exam systems.